2023
DOI: 10.1017/ash.2022.330
|View full text |Cite
|
Sign up to set email alerts
|

Decreased hospital readmissions after programmatic strengthening of an outpatient parenteral antimicrobial therapy (OPAT) program

Abstract: Objective: To determine whether a structured OPAT program supervised by an infectious disease physician and led by an OPAT nurse decreased hospital readmission rates and OPAT-related complications and whether it affected clinical cure. We also evaluated predictors of readmission while receiving OPAT. Patients: A convenience sample of 428 patients admitted to a tertiary-care hospital in Chicago, Illinois, with infections requiring intravenous antibiotic therapy after hospital discharge. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…Investigators at an urban academic center also reported readmissions due to disease worsening or progression as well as line-associated issues prior to the implementation of an OPAT program and saw a significant reduction in the readmission rates following the integration of a structured OPAT program. 7,12 Also, patients residing in highly vulnerable areas are at an increased risk for complications following hospital discharge leading to rehospitalization, which is consistent with the results presented in our study. 17 journals.sagepub.com/home/tai…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Investigators at an urban academic center also reported readmissions due to disease worsening or progression as well as line-associated issues prior to the implementation of an OPAT program and saw a significant reduction in the readmission rates following the integration of a structured OPAT program. 7,12 Also, patients residing in highly vulnerable areas are at an increased risk for complications following hospital discharge leading to rehospitalization, which is consistent with the results presented in our study. 17 journals.sagepub.com/home/tai…”
Section: Discussionsupporting
confidence: 92%
“…5,6 The involvement of a multidisciplinary ID team in an established OPAT program has been shown to reduce antimicrobial prescribing errors. 7 Through collaboration with home health services, the dedicated OPAT/COpAT program can enhance the continuity of care by optimizing the duration of antimicrobial therapy pre-discharge and improving safety monitoring by receiving and responding to critical laboratory results postdischarge. Nonetheless, there is limited data that describes the utility of pre-and post-discharge OPAT/COpAT programs in optimizing patient care, particularly in socially vulnerable communities where inequities in healthcare access have detrimental outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…With the introduction of the OPAT service, a prospective data collection was started thus facilitating the assessment of clinical response to antimicrobial treatment and monitoring of adverse events related to devices and antibiotic use. Moreover, our approach with the integration of ID consultation service, OPAT and stewardship could be a role model towards the implementation of other OPAT services, emphasizing also the mandatory interprofessional approach including ID experts, nurses as well as clinical pharmacists [27,28]. Our study has limitations.…”
Section: Discussionmentioning
confidence: 99%
“…As health care continues to move toward more cost-conscious, value-based care, our experience supports the need for appropriate infrastructure and resources to achieve these goals. OPAT can reduce length of stay, readmissions, and ED visits [ 2 , 3 , 12 ], although recent data demonstrate the need for appropriate infrastructure and an expert multidisciplinary team to best support state-of-the-art practice [ 26 ]. Furthermore, OPAT may be a model for fee-for-value compensation, especially with care moving into ambulatory and nontraditional settings [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its numerous benefits include improved patient quality of life over inpatient care and hospital cost savings [ 1 ]. OPAT programs decrease health care utilization by lowering the number of inpatient days, emergency department (ED) visits, and hospital readmissions [ 2 , 3 ]. Increases in ED visits and hospital readmissions further strain ED and hospital resources, which can be financially burdensome to the health care system [ 1 ].…”
mentioning
confidence: 99%